Mycology-Nanotechnology Interface: Applications in Medicine and Cosmetology - Dhanjal, Daljeet Singh; Mehra, Parul; Bhardwaj, Sonali; Singh, Reena; Sharma, Parvarish; Nepovimova, Eugenie; Chopra, Chirag; Kuca, Kamil (International journal of nanomedicine, 2022)
In today's time, nanotechnology is being utilized to develop efficient products in the cosmetic and pharmaceutical industries. The application of nanotechnology in transforming bioactive material into nanoscale products substantially improves their biocompatibility and enhances their effectiveness, even when used in lower quantities. There is a significant global market potential for these nanoparticles because of which research teams around the world are interested in the advancements in nanotechnology. These recent advances have shown that fungi can synthesize metallic nanoparticles via extra- and intracellular mechanisms. Moreover, the chemical and physical properties of novel metallic nanoparticles synthesised by fungi are improved by regulating the surface chemistry, size, and surface morphology of the nanoparticles. Compared to chemical synthesis, the green synthesis of nanoparticles offers a safe and sustainable approach for developing nanoparticles. Biosynthesised nanoparticles can potentially enhance the bioactivities of different cellular fractions, such as plant extracts, fungal extracts, and metabolites. The nanoparticles synthesised by fungi offer a wide range of applications. Recently, the biosynthesis of nanoparticles using fungi has become popular, and various ways are being explored to maximize nanoparticles synthesis. This manuscript reviews the characteristics and applications of the nanoparticles synthesised using the different taxa of fungi. The key focus is given to the applications of these nanoparticles in medicine and cosmetology.
Keywords: fungi; nanotechnology; technologie zelené chemie; houby; kovové nanočástice; nanotechnologie; Mycology; mykologie; nanoparticles; Green Chemistry Technology; Fungi; biological application; Nanotechnology; Metal Nanoparticles; biosynthesis